Penerapan Goal Directed Design dalam Perancangan Ulang User Interface pada Admin Marketplace BUILD ID - Helmalia Sandy; Pacu Putra; Allsela Meiriza; Nabila Rizky Oktadini; Putri Eka Sevtiyuni (Journal of Information System Research (JOSH), 2023)
Build Id is a website and application-based marketplace that provides various construction needs, both products and services. The Build Id design by PT Semen Baturaja Tbk is aimed at the community as a form of implementing digital transformation in Indonesia. But the design process, to requires evaluation and improvement before it is inaugurated. This is done to avoid complaints, which can reduce the performance of applications and companies. This study aims to help design the Build Id user interface so that it is more focused on the features to be implemented so that the results can match the user's needs. In testing, this study uses the Goal Directed Design method which focuses on designing application designs by identifying user goals and needs. The results of the test prove that the Build Id marketplace for Admins is running well and as expected.